Perceptions of Quality of Service analysis Jampersal By Village Midwife Inpuerperal women in Semarang District Region - Wien Soelistyo Adi; Bahiyatun Bahiyatun; Umaroh Umaroh (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Jampersal program is expected to maternal health care delivery place. Midwives as the front line to provide care to pregnancy, childbirth and postpartum, and providing care to the newborn. This is expected to reduce the number of maternal and infant mortality.This study aims to describe perception postpartum jampersal ministry.This research was a descriptive study with a qualitative approach in Semarang district, population was postpartum user jampersal the midwives care unit Semarang District Region. Sampling technique used a purposive sample of 16 women was childbirth.Includes direct evidence, reliability, responsiveness, assurance, empathy of service hours jampersal of midwife care giver. The results showed tangible aspects largely to meet the standard, there are midwives do not comply with the provisions of the room and preparation tools. Aspects of reliability was most appropriate procedure, there were midwives who do not fit postpartum care procedures. Aspects of responsiveness (responsiveness) most midwives have responded well, there is a small part do not care in accordance with procedures. Aspects of assurance all midwives had done according to the procedure. Aspects of empathy all midwives were providing services to empathize. Direct observation infrastructure most midwives had good infrastructure, there was a small facility and infrastructure in accordance with the procedure midwife yet.Suggestions: Semarang District Health Office should improve the supervision and evaluation of service standard postpartum care by midwives village jampersal caregivers. Midwives should provide maternity care postpartum jampersal users in accordance with standards established by the District Health Office Semarang